2010
DOI: 10.1017/s0020818310000214
|View full text |Cite
|
Sign up to set email alerts
|

Goliath's Curse: Coercive Threats and Asymmetric Power

Abstract: States typically issue compellent threats against considerably weaker adversaries, yet their threats often fail. Why? Expanding on a standard model of international crisis bargaining, I argue that a theory of reputation-building can help shed light on this puzzle. The model casts reputation as a strategic problem, showing that challengers issuing compellent threats have incentives to anticipate the reputation costs that target states incur when appeasing aggressors. If challengers can recognize these costs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…See Alt, Calvert, and Humes 1988;Nalebuff 1991;and Sechser 2010. the other hand, they cannot predict precisely the point at which the defender will move from acquiescing to ever-more stringent demands to preferring to fight. Challengers thus face a risk-return tradeoff, in which higher demands increase the probability of war, but also increase the benefits associated with peace should the defender acquiesce.…”
Section: Reputation Proponentsmentioning
confidence: 99%
“…See Alt, Calvert, and Humes 1988;Nalebuff 1991;and Sechser 2010. the other hand, they cannot predict precisely the point at which the defender will move from acquiescing to ever-more stringent demands to preferring to fight. Challengers thus face a risk-return tradeoff, in which higher demands increase the probability of war, but also increase the benefits associated with peace should the defender acquiesce.…”
Section: Reputation Proponentsmentioning
confidence: 99%
“…It has been suggested that the reputational costs involved in submitting to foreign pressures are key to understanding why coercive threats by stronger states can fail to achieve their objectives over weaker states (Sescher 2010).…”
Section: Policy Transfer National Reputation and Hypocrisy Costsmentioning
confidence: 99%
“…Sartori 2005;Sechser 2010). If analyzed from the perspective of the policy makers for whom retaining office is an important if not paramount concern, the domestic political consequences of international crises are extremely pertinent (Bueno de Mesquita and Siverson 1995).…”
Section: Audience Costs and Crisis Bargaining: Theory And Testsmentioning
confidence: 99%